Digital Platforms and the Marginalization of MSMEs: An Islamic Economic Law Perspective in Parepare City - Sofyan Ahmad; Zainal Said; Hannani Hannani (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2026)
Research on MSMEs and the digital economy generally focuses on digital marketing strategies and the validity of contracts in electronic transactions, while studies on the marginalization of MSMEs due to the structure and policies of digital platforms are still relatively limited. This study aims to analyze the marginalization mechanisms of Micro, Small, and Medium Enterprises (MSMEs) in the digital platform ecosystem and examine this phenomenon from the perspective of Islamic Economic Law. The study was conducted in Parepare City, South Sulawesi, using a descriptive qualitative research method with a field study approach. Data were obtained through in-depth interviews, observation, and documentation of nine MSMEs consisting of Culinary Businesses, Local Craft Businesses, Muslim Fashion Businesses, printing businesses, mixed shops, fried food businesses, Sultan Snacks, laundry, and graduation sash businesses. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show that digital platforms provide benefits in the form of expanded market access, increased consumer reach, and ease of transactions. However, on the other hand, marginalization mechanisms were found, characterized by dependence on platform algorithms, high service and promotion costs, the dominance of large-capital businesses, unequal price competition, and a lack of transparency in platform policies. From the perspective of Islamic Economic Law, this situation does not fully reflect the principles of justice (al-'adl), balance (tawazun), and public welfare (maqasid sharia). Furthermore, there are indications of elements of gharar (unlawful behavior) due to unclear algorithms and platform policies, which have the potential to harm MSMEs. Therefore, more transparent, accountable digital regulations are needed that support the protection and empowerment of MSMEs. Keywords: MSMEs, Digital Platforms, Economic Marginalization, Islamic Economic Law, Fiqh Muamalah, Maqasid Sharia